Use substitution and substitute y into the other equation. One of the equations already gives you y in terms of x, so use that and substitute it into the other equation. y = 3x - 4
Plug into the other equation: -3y = -9x + 12
-3(3x-4) = -9x + 12
-9x + 12 = -9x + 12
This is an identity. So that means that any value of x makes this equation true. So B.
Yes the correct answer is D. Hope this helps :)
Hey, so basically just plug in the x values for x in the equation. First table the first x value is -1 so just plug it in to 3x so: 3(-1)= -3. That’s your y.
Answer:
x = 4
Step-by-step explanation:
First you would add those 2 equations, which would be 43x + 8. Then you make it equal to 180, so 43x + 8 = 180. Subtract 8 from both sides, and divide 43 from both sides.